“THE BURIED GIANT” BY KAZUO ISHIGURO: THE POSTMODERN DILEMMA OF REMEMBRANCE AND FORGIVENESS - Victoria I. Lipina; Glib V. Lipin (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The article focuses on the study of the seventh novel “The Buried Giant” (2015) of the Nobel Prize laureate Kazuo Ishiguro with regard to the problems of remembrance and forgiving that are central to the ethics of memory. Disputes about this novel go both in his country and abroad. The novel was translated into Ukrainian (2018), although the integrated study of the artistic nature of this iconic work has not appeared yet. The goal of our work and the tasks dictated by it is to analyze the artistic idea of the novel in the context of modern ethical and philosophical discourse on memory and forgiveness, which pervades Ishiguro’s works, starting from his first “Japanese” novels centered on the unnamed loss. The interest in memory as ethical issue has recently inspired different branches of the Humanities. The phenomenology of memory and oblivion was considered in the works of S. Radson “Memory and Methodology”, the collective monograph “Memory theory”, in the works of P. Ricoeur, M. Foucault, J. Baudrillard, J. Derrida, P Nora, H. White, M. Merleau-Ponty, and others, and resonated in literature of the second half of the twentieth century after the tragic events of the Second World War. This theme preoccupied Ishiguro throughout much of his writings, starting with his “Japanese” novels “A Pale View of the Hills” and “An Artist of the Floating Worlds”. The goal of the paper determines the need to use two methodologies and methods ‒ a historical and literary study in combination with semantic and poetological analysis of the text, which is based on the post-structuralist methodology, a new awareness of the depth and inexhaustibility of the literary text when it starts to contradict itself. In the novel, the role of memory in the life of individuals is artistically problematized. Memory is revealed not as the cornerstone of human morality and truth, but as a possible choice between healing forgetting and difficult forgiving, that are also inherent in the lives of humanity. The plot is centred on artistic deployment of an insoluble dilemma addressed to us as well: memory or oblivion, and maybe forgiveness? But how is it possible to forget the severe massacre in the past? Does the reconciliation with the terrible past equal treachery and betrayal? In this novel, in contrast to the previous ones, the writer finds a different generic decision, connecting the chivalrous plot and heroic epic with a saturated philosophical-humanistic agenda. This artistic strategy is noticeably different from his former novels. Its meaningful and indirect suggestive narrative unveils the most difficult issues of human responsibility in the history. The tragedy of both the historical and personal experience of mankind suggested this idea for the novel.